The Effect of Front-Desk Roleplay in Enhancing Hospitality Students' Speaking Skills - Safira Nur Azizah; Nur Fauzia (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to examine the effect of front-desk roleplay in enhancing hospitality students’ speaking skills at the vocational high school level (SMK). The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design, involving thirty (30) hospitality major students who participated in the front-desk roleplay treatment. Data were collected using speaking skill tests administered before and after the treatment. The data were analyzed using descriptive statistic and statistical analysis such as paired sample t-test and effect size. The results showed significant improvement in hospitality students’ speaking skills after the implementation of front-desk roleplay treatment. The mean score of the pretest was 67.5, which increased to 77.8 in the posttest, indicating a gain of 10.3 points. Paired sample t-test also demonstrated a significant difference between pretest and posttest scores with p-value less than 0.05. Furthermore, the effect size was > 0.8, indicating a large effect based on Cohen’s criteria and suggesting that the treatment had a large effect on students’ speaking performance. Therefore, front-desk roleplay treatment can be considered an effective learning strategy for improving students’ speaking skills. By using front-desk roleplay, students engage in simulated real-life hotel scenarios that make the learning process more meaningful, create authentic learning experiences, and align with the actual communication demands of the hospitality industry.